VHF field strength measurements in mountainous terrain study of reflection effects - Rao, B.L.N.; Roys, B. K.; Mathur, H. B.; Gupta, U. C. (Defence Science Journal, 2014)
Effects of reflection on the field strength of very high frequency radio-waves in mountain us terrain have been studied. Experiment on diffraction paths in mountainous area were made at 126 Mc/by varying antenna height from 1.8mtp 3.75m for both vertically and horizontally polarised waves. The results showed no significant reflection effects as there were no maxima and minima in received field strength with variation of antenna height.It has been concluded that reflection effects can be neglected for many practical purposes of communication over short distances in mountainous terrain area having considerable vegetation over the path.